PENGARUH FINANCING TO DEPOSIT RATIO (FDR) DAN NON PERFORMING FINANCING (NPF) TERHADAP RETURN ON ASSET (ROA) PADA PT. BANK SYARIAH MANDIRI. - Alim, Syahirul; Asyari, Jauhar Maqnun (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
Return On Assets (ROA) is the company's ability to gain overall profits. The greater the level of Return on Assets (ROA) of a bank, the better the bank in terms of asset use. the purpose of this study is to determine whether the variable Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) partially and simultaneously affect the Return On Assets (ROA) at PT. Bank Syariah Mandiri. This research is included in quantitative research. The type of data used is secondary data obtained from the official website of Bank Syariah Mandiri. Data collection conducted at Bank Syaraih Mandiri includes quarterly financial report in 2010 until 2017, consisting of balance sheet, income statement and report in the form of ratio. In this study the method used in analyzing is multiple linear regression using SPSS 23 statistical software. Based on the result of the research, it can be concluded that partially variable Financing To Deposit Ratio (FDR) positively influence to Return On Asset (ROA), positive influence in the sense if FDR variable increase, similar with ROA variable. On the other hand Non Performing Financing variable negatively affect Return On Assets (ROA),. Negatively, if the NPF increases, it will create a play on return on asset (ROA). Simultaneously, the two variables which include Financing to Deposit (FDR) and Non Performing Financing (NPF) give significant influence to Return On Assets (ROA), both variables give significant effect that is equal to 89,10%.